ChemInform Abstract: Bifunctional Furfuryl Cations Strategy: Three‐Component Synthesis of Enamidyl Triazoles. Issue 21 (6th May 2016) - Yang, Hengtuo; Gou, Jing; Guo, Jiawei; Duan, Dongyu; Zhao, Yu‐Ming; Yu, Binxun; Gao, Ziwei
Abstract: A three‐component reaction based on a furan platform strategy is accomplished under stoichiometric Lewis acid promotion.